KymoRod: a method for automated kinematic analysis of rod‐shaped plant organs. (8th September 2016) - Bastien, Renaud; Legland, David; Martin, Marjolaine; Fregosi, Lucien; Peaucelle, Alexis; Douady, Stéphane; Moulia, Bruno; Höfte, Herman
Summary: A major challenge in plant systems biology is the development of robust, predictive multiscale models for organ growth. In this context it is important to bridge the gap between the, rather well‐documented molecular scale and the organ scale by providing quantitative methods to study within‐organ growth patterns. Here, we describe a simple method for the analysis of the evolution of growth patterns within rod‐shaped organs that does not require adding markers at the organ surface. The method allows for the simultaneous analysis of root and hypocotyl growth, provides spatio‐temporal information on curvature, growth anisotropy and relative elemental growth rate and can cope with complex organ movements. We demonstrate the performance of the method by documenting previously unsuspected complex growth patterns within the growing hypocotyl of the model species Arabidopsis thaliana during normal growth, after treatment with a growth‐inhibiting drug or in a mechano‐sensing mutant. The method is freely available as an intuitive and user‐friendly Matlab application called KymoRod. Significance Statement: Connecting molecular networks to organ growth requires a way to automate analysis of intra‐organ growth patterns. Here we use KymoRod to uncover previously unsuspected complexity in Arabidopsis hypocotyl growth patterns and to confirm the role of mechano‐sensing in the supra‐cellular coordination of cell expansion.